Flexible Media Polishing Machine for Ti-6Al-4V Components - de Jongh, Quintin Oliver (Department of Mechanical Engineering, 2023)
New-age components (notably those in the bio-medical and aerospace industries) are often manufactured from hard to machine materials such as Ti-6Al-4V and tungsten carbide and have extreme surface finish requirements. Flexolap polishing offers a technique to achieve these requirements, and minimizes the disadvantages encountered by other polishing techniques. The aim of this dissertation is that of designing and developing a working Flexolap polishing machine (and associated abrasive compound) suitable for the South African manufacturing industry (and any industry with a lack of financial means and skills for advanced manufacturing). This aim was affirmed by developing models to characterize the Flexolap polishing process, as well as by using experimental analysis to verify the process viability and compatibility with Ti-6Al-4V (and subsequently, other easier to machine materials). A thorough literature review is presented with the most important conclusions of optimal polishing conditions (high hydration, high media impinging velocity and a 45º polishing angle) and applicable modelling methods (momentum, critical values, and vibrational analysis). Two models (empirical and analytical) and a supporting simulation model are presented for force control and stipulation of required conditions for ductile regime polishing to occur. A third model is presented later in the dissertation and classifies the viscoelastic nature of the designed abrasive as well as its damping effect as the compounded media is hydrated (the media-workpiece interaction becomes more underdamped). The results of all modelling processes provide proof that effective polishing can be achieved at designed working conditions (times of less than 10 minutes to desired surface roughness and contact stresses less than that for brittle failure but greater than that required to induce ductile regime polishing). The process of creating/building the Flexolap machine is described through design and development. Process calculations to support design include belt and pulley calculations, bearing calculations, steady abrasive/air flow calculations and weld strength calculations. Experimental techniques include gathering force data (using a dynamometer) and finding surface properties (using a profilometer and various microscopes). This led to gathering a large set of results which were used to study the process viability. Analysis is based on surface roughness and texture change over time (or change over other parameters), as well as the changes in force over parameters such as media hydration, media diamond concentration and media velocity. Experimental results display trends of polishing forces decreasing with an increase in hydration, while surface roughness decreases in a logarithmic manner (with a great initial decrease before reaching a convergence point). Surface texture is also shown to improve with a lesser presence of asperities and a more uniform texture overall (with greater hydration levels). Higher impinging velocities lead to lower surface roughness being achieved quicker while higher diamond concentration tends to create higher roughness at higher impinging velocities. Medium-high media hydration (30%), higher impinging velocities (31.4 m/s) and a polishing angle of 45º are proven to be the most effective polishing conditions. The study was successful in proving the viability and effectiveness of the Flexolap polishing technique while also providing pertinent experimental and theoretical data towards the further study of the process. The expected benefits the outcomes of this study provide to industry are: an easy to learn finishing process that can easily integrate into a finishing or manufacturing workshop (thus upskilling operators), an efficient and cost effective means of polishing hard to machine materials (reducing cycle time and cost), and a framework of polishing machine that can be easily adjusted to meet industry needs for example: size/shape of workpiece and automation of the process. This study was embarked on due to the lack of inexpensive and easy to operate polishing methods available in South Africa, particularly because raw titanium is often exported for processing due to the low availability of advanced manufacturing equipment for the material in South Africa as well as the low level of operator experience in advanced manufacturing machinery.